Research on work values in Malaysia and Thailand: a cross-cultural research proposal - Abdul Rahman, Wan Rafaei (2007)
The aim of this research is to examine the similarities and differences of work values in Malaysia and Thailand. The relationship between ethnic culture, work culture, organizational citizenship behavior (OCB), job satisfaction, organizational commitment, and productivity, as well as sex, marital status, age, academic qualification, duration of service and monthly income will also be analyzed. The participants for this study are 900 primary school teachers, of which will be divided into 3 groups of 300 participants selected from, Kuala Lumpur, Alor Setar and Bangkok, Thailand. The work value scale used will be from the scale developed by Wan Rafaei Abdul Rahman and Che’ Su Mustaffa (2004), The Twelve Pillars of Malaysia, and The Nine Thai values of orientation (Komin, 1995).